COVID-19 vaccination status and willingness for further booster doses among staff and students of a tertiary care institute - Thakare, Meenal Madhukar; Sharma, Nikita; Karol, Sunidhi (Indian Journal of Community Health, 2025)
Background: Vaccination remains the mainstay of COVID-19 prevention. While initial vaccine acceptance was high among healthcare workers (HCWs), the emergence of new variants and waning immunity necessitated vaccine boosters. The study aimed to ascertain the COVID-19 vaccination status of the staff and medical students of a tertiary care institute and their willingness for further booster doses. Methods: An observational study was conducted among healthcare workers (doctors, nurses, technicians), ancillary staff, and students. An online semi-structured questionnaire collected information from participants regarding sociodemographic characteristics, history of COVID-19 vaccination, acceptance and uptake of booster dose, and reasons for willingness to uptake booster. The Chi-square test assessed the association between sociodemographic variables and booster acceptance. Results: About 302 people filled the survey questionnaire. Most of the participants belonged to the 18-29 year age group (61.3%) and worked in the clinical departments (54.3%). The majority of them had received the Covishield vaccine (71.5%). Half of them had already received a COVID-19 booster. Seven out of ten participants were willing to uptake further vaccine booster. Being a healthcare worker and working in non-clinical department was significantly associated with booster acceptance. The perception of the COVID-19 vaccine as an immunity booster was a key motivator. About 15.1% of participants expressed a preference for a nasal booster for its convenience in administration. Conclusion: The study highlights a high willingness for COVID-19 vaccine boosters among healthcare professionals and medical students. It emphasizes the importance of continuous efforts to promote vaccine boosters, given the crucial role of the medical community in shaping public perception.